A FancD2-monoubiquitin fusion reveals hidden functions of Fanconi anemia core complex in DNA repair. - Matsushita, N; Kitao, H; Ishiai, M; Nagashima, N; Hirano, S; Okawa, K; Ohta, T; Yu, D; McHugh, P; Hickson, I; Venkitaraman, A; Kurumizaka, H; et al. (2005)
In DNA damage responses, the Fanconi anemia (FA) protein, FancD2, is targeted to chromatin and forms nuclear foci following its monoubiquitination, a process likely catalyzed by the FA core complex. Here, we show that a chicken FancD2-ubiquitin fusion protein, carrying a Lys-Arg substitution removing the natural monoubiquitination site (D2KR-Ub), could reverse cisplatin hypersensitivity and localize to chromatin in FANCD2-deficient DT40 cells. Importantly, the chromatin targeting was dependent on three core complex components as well as the hydrophobic surface of ubiquitin that may direct protein-protein interactions. Furthermore, a constitutively chromatin bound fusion of D2KR-histone H2B could complement cisplatin sensitivity in FANCD2- but not FANCC-, FANCG-, or FANCL-deficient cells. Thus these core complex components have an additional function in the DNA repair, which is independent of the monoubiquitination and chromatin targeting of FancD2. These results define functional consequences of FancD2 monoubiquitination and reveal previously hidden functions for the FA protein core complex.